A Caribbean New Urban Agenda post-Habitat III: Closing the gaps. (November 2017) - Mycoo, Michelle A.
Abstract: Urbanisation, climate change and natural hazards present serious challenges for the Caribbean which Habitat III brought into focus. This paper critically examines problems associated with these complex challenges, to propose a relevant Caribbean specific New Urban Agenda and suggest implementation mechanisms which are essential to forge ahead. It reviews urban issues for fifteen countries that constitute the Caribbean Community (CARICOM). These problems are investigated from the perspective of four pillars of economic, social and environmental sustainability, and governance. The paper reveals that with the application of these main components and related thematic elements, many countries in this grouping are underperforming in achieving the sustainable development goal of safe, resilient and sustainable urban settlements. The main conclusion drawn is that countries of the CARICOM Caribbean should not adopt an imported blueprint to resolve critical urban issues. This is an opportune time for crafting a relevant indigenous New Urban Agenda for CARICOM Caribbean countries and finding the right implementation mechanisms to be at the frontline of change.